Associations between organophosphate flame retardants metabolites in follicular fluid and reproductive outcomes among women undergoing IVF/ICSI treatment in Southwest China - Xiaohong Li; Jiahui Qiu; Zhiwei Gan; Shangwei Li; Xun Zeng (Reproductive Biology and Endocrinology)
Abstract Background Previous studies suggest organophosphate flame retardants (OPFRs) negatively affect fertility, but limited research explores their metabolites in follicular fluid and reproductive outcomes. Objectives To investigate the associations between concentrations of OPFRs metabolites in follicular fluid and the outcomes of in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) among women undergoing treatment. Methods Women who underwent IVF/ICSI treatment at the Reproductive Center of West China Second University Hospital, Sichuan University, China, from 2017 to 2020 were recruited. The levels of seven OPFRs metabolites were quantified in follicular fluid collected on the day of oocyte retrieval. Reproductive outcomes were assessed, including key IVF/ICSI outcomes. Results This study included 401 women. After adjusting for relevant confounders, elevated concentrations of BBOEP (β = -0.08, 95% CI: -0.12 to 0 0.05), BEHP (β = -0.11, 95% CI: -0.17 to 0.05), DnBP (β = -0.23, 95% CI: -0.37 to 0.08), and DPhP (β = -0.12, 95% CI: -0.18 to 0.06) in follicular fluid were inversely associated with the number of good embryos on day 3. Elevated BEHP concentrations were negatively associated with the total number of oocytes (β = -0.04, 95% CI: -0.07 to 0.01). In comparison with the lowest tertile, the highest tertile of DnBP was associated with a 42% reduction in biochemical pregnancy (p-trend = 0.05). Furthermore, the BKMR models revealed inverse associations between OPFRs metabolites mixtures and the number of good embryos. Conclusion Findings suggest OPFRs may negatively affect IVF/ICSI outcomes, warranting further study on environmental impacts on fertility.